Annual Report 2022 of Current Applied Science and Technology - Dusanee Thanaboripat (My University, 2022)
In the year 2022, the journal published 90 articles in Vol. 22 Nos. 1-6. There are 9 articles from KMITL, 31 articles from outside KMITL and 50 articles from overseas. Comparison of manuscripts submitted for publication in 2019, 2020 and 2021 are shown in Figure 1. The number of manuscripts submitted increased from 244 in the year 2020 to 374 and 382 articles in the year 2021 and 2022, respectively while the acceptance rates in 2020-2022 are 27.89%, 15.95% and 10.84%. The top ten countries of authors submitting manuscripts to be published in the journal in 2022 are shown in Figure 2, where Thailand (28.43%), India (19.44%) and Indonesia (12.58%) are among the top three countries. Figure 3 shows the average duration process for publication during 2020-2022. The average duration processes from received to accepted dates are 110.91, 162.98 and 199.82 days in 2020, 2021, 2022, respectively. Due to the change of the submission system in 2021 and 2022, average duration process was much longer than in 2020. The subject area and category of published articles in 2022 according to SJR are in 3 categories: 1) Agricultural and Biological Sciences (Agricultural and Biological Sciences (miscellaneous) and Agronomy and Crop Science), 2) Biochemistry, Genetics and Molecular Biology (Biotechnology) and 3) Environmental Science (Environmental Engineering). Scopus cite score and SCImago journal rank of the journal in 2020-2022 are shown in Figure 4. The cite score increased from 0.3 in 2020 to 1.1 in 2022 (last update on 6 Dec 2020). However, SCImago journal rank in 2022 has not been reported yet. In addition, the most cited article in Scopus is “Chicken Feathers Based Keratin Extraction Process Data Analysis Using Response Surface-Box-Behnken Design Method and Characterization of Keratin product” published in 2020 followed by “Characterization, Functionality and Antioxidant Activity of Water-Soluble Proteins Extracted from Bombyx Mori Linn.” published in 2018 and “Antimicrobial Activity of Edible Electrospun Chitosan/Cellulose Acetate/Gelatin Hybrid Nanofiber Mats incorporating Eugenol” published in 2019. The most cited article in TCI is “Antibacterial Activity of Crude Ethanolic Extracts and Essential Oils of Spices Against Salmonellae and Other Enterobacteria” published in 2005 followed by “Preparation of Red Yeast Rice Using Various Thai Glutinnous and Monascus purpureus CMU001 Isolated from Commercial Chinese Red Yeast Rice Sample” published in 2007 and “Importance of Aflatoxins” published in 2002.
Keywords: Web of science; Bee Products Chemical Analysis